The role of social media support as public health intervention strategy in Indonesia - Pande Putu Januraga (Universitas Udayana, 2017)
Finally, with the growing and high number of internet and social media users, it could be concluded that Indonesia is a potential country for the development of internet-social media based health intervention.18 Currently, there are abundant programs and/or campaign using internet and social media based as platforms for health information and promotion, however most of them were developed without proper evaluation design to measure its effectiveness. Universities and research centers in the country could become a potential partner for any developers for developing programs and/or campaigns that utilize internet and social media in standardized and scientific ways.